Immunization Visit Delay in Children Aged 0-24 Months During The Covid-19 Pandemic in Greater Jakarta - Istianah Surury; Siti Riptifah Tri Handari (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
The COVID-19 pandemic since the beginning of 2020 has had a significant impact on other essential health services. One of them is the immunization service. Jakarta, Depok, Tangerang, and Bekasi, or Greater Jakarta is the epicenter of the spread of COVID-19 in Indonesia. This study aimed to find the distribution of immunization delay in women with children aged 0-24 months and its reasons in Greater Jakarta. This study used an observational method with a cross-sectional study design. The research process was carried out for six months, from June to November 2020, and 274 samples were collected through online google forms. The study found the proportion of mothers who delayed their children's immunization was 48,9%. The most common reasons are fear of being infected with COVID-19, health facilities not providing immunizations for children, limited vaccine availability, and declining family income during the pandemic. The government should increase the promotion of primary immunization to the community and ensure the availability, safety, and implementation of health protocols in health care facilities.